2021
DOI: 10.3390/catal11020219
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Loaded Mesoporous MCM-41 for the Catalytic Wet Peroxide Oxidation (CWPO) of Acetaminophen

Abstract: MCM-41 based catalysts (molar ratio Si/Al = 40) were prepared by a hydrothermal route, modified by ionic exchange with different metals (Cu, Cr, Fe and Zn) and finally calcined at 550 °C. The catalysts were fully characterized by different techniques that confirmed the formation of oxides of the different metals on the surfaces of all materials. Low-angle X-ray diffraction (XRD) analyses showed that calcination resulted in the incorporation of metallic Zn, Fe and Cr in the framework of MCM-41, while in the cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 86 publications
1
12
0
Order By: Relevance
“…41 In addition, the enhancement of the pore diameter of promoted and unpromoted samples compared to that of the parent material was a result of the integration of the nanoparticles into the support structure throughout the heat treatment. 42 It should be noted that among all the samples, the pore volume of Ba(5%)/Ni(15%)@MCM-41 was the smallest (0.31 cm 3 g −1 ), which indicated that a significantly larger amount of metal atoms were anchored in the hexagonal mesopores of MCM-41. 39 The surface properties and morphology of the prepared samples were explored via SEM analysis (Fig.…”
Section: Characterization Of the Prepared Materialsmentioning
confidence: 90%
“…41 In addition, the enhancement of the pore diameter of promoted and unpromoted samples compared to that of the parent material was a result of the integration of the nanoparticles into the support structure throughout the heat treatment. 42 It should be noted that among all the samples, the pore volume of Ba(5%)/Ni(15%)@MCM-41 was the smallest (0.31 cm 3 g −1 ), which indicated that a significantly larger amount of metal atoms were anchored in the hexagonal mesopores of MCM-41. 39 The surface properties and morphology of the prepared samples were explored via SEM analysis (Fig.…”
Section: Characterization Of the Prepared Materialsmentioning
confidence: 90%
“…Adsorption rate constants were determined using collision theory as k normala = 1000 A N normalA 4 [ g a s ] ( 8 R T π M ) 1 / 2 where R is the gas constant, T is the temperature, M is the molar mass, A is the area of the active site (1.27 × 10 –18 m 2 ), and [gas] is the concentration of the adsorbing methane or methanol molecules. The rate of photoactive MO x species activation is calculated by k normala normalc normalt = normalΦ w I 2 h c ( λ f 2 λ i 2 ) ( w t % ) where Φ is the quantum yield, I is the photon intensity, w is the weighting factor for the percentage of the incident photons irradiating the photocatalyst that are in a specific wavelength range, h is Planck’s constant, c is the speed of light, (λ f 2 – λ i 2 ) gives the range of photon wavelengths that will activate the photocatalyst, and the wt % factor is the experimental weight percent of metal loading for each of the transition metals doped into the MCM-41 amorphous SiO 2 (1.91% for Cr, 3.5% for Nb, 20.0% for W). ,, The Cr, Nb, and W MO 4 /MCM-41 materials activate under UV light giving w = 0.05 to account for the 5% of total solar irradiation in the UV range λ f = 400 nm and λ i = 100 nm. I is measured as 1370 W m –2 for solar irradiance, , while Φ is set as a stochastic array of activation percentages to observe the changes to the POM mechanism on the MO 4 /MCM-41 materials during the MKM simulations.…”
Section: Methodsmentioning
confidence: 99%
“…In this article, we elucidate the photoexcitation manifolds and properties along with the POM mechanisms of single-site photocatalysts based on CrO 4 , NbO 4 , and WO 4 embedded on the surface of MCM-41 amorphous SiO 2 micropores. These three metals were chosen because they are close to vanadium to allow a comparison in the properties, have been synthesized previously, are in groups 5 and 6 where a number of oxidation states are possible, and cover the first three periods of the transition metal series. We first describe the computational methodology used in this study.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, oxalic acid, formic acid, and acetic acid were the main transformation products when metal-loaded mesoporous for the catalytic wet peroxide oxidation of ACT. 35 Fenton oxidation applied by De Luna et al 75 to degrade ACT. The by-products were hydroquinone, benzoic acid, benzaldehydes and some non-aromatic products like carboxylic acid, alcohols, ketones, and aldehydes.…”
Section: By-products Of Actmentioning
confidence: 99%